2022
DOI: 10.2478/foli-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Inflation, Inflation Uncertainty and the Economic Growth Nexus: A Review of the Literature

Abstract: Research background: Price stability plays a crucial role in ensuring stabilities in the financial markets as well as the real sector. Despite this, questions are still raised, querying if it is either inflation, inflation uncertainty or a combination of both, which affects economic growth? The results obtained, both theoretically and empirically, differ. This paper seeks to revisit and provide both the theoretical and empirical review of literature on the inflation, inflation uncertainty and economic growth n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 69 publications
3
5
0
Order By: Relevance
“…In fact, an increase of 1% of INF decreases economic growth by 1.8%. This result is similar to the results presented by Hu et al (2022), Mandeya and Ho (2022), and Sequeira (2021), who found that inflation negatively harms economic growth in both the short and long run. On the other hand, adverse economic effects dominate if inflation rises faster.…”
Section: Resultssupporting
confidence: 92%
“…In fact, an increase of 1% of INF decreases economic growth by 1.8%. This result is similar to the results presented by Hu et al (2022), Mandeya and Ho (2022), and Sequeira (2021), who found that inflation negatively harms economic growth in both the short and long run. On the other hand, adverse economic effects dominate if inflation rises faster.…”
Section: Resultssupporting
confidence: 92%
“…In the latest research, analysts are faced with the inexplicable phenomenon of inflation and its uncertainty due to the expectations. Mandeya and Ho (2022) conducted research that referred to the impact of inflation and inflation uncertainty. They found that the effects of inflation are strongest in the case of uncertainty regarding the price-informative channel.…”
Section: Inflationary Pressures and Inflationary Trends In The Emergi...mentioning
confidence: 99%
“…Studies on the impact of inflation on economic growth can be positive (Uddin 2022) or negative (Anghelache et al 2021), or even mixed or inconclusive (Mandeya 2021). Yilmazkuday (2022), found that the strength of institutions tends to influence the results; 'While the effects of inflation on growth are negative and significant in countries with stronger institutions, they are positive and significant in countries with weaker institutions.'…”
Section: ▪ Inflationmentioning
confidence: 99%
“…Yilmazkuday (2022), found that the strength of institutions tends to influence the results; 'While the effects of inflation on growth are negative and significant in countries with stronger institutions, they are positive and significant in countries with weaker institutions.' However, (Mandeya 2021), makes a good contribution in a literature review in which he shows that the outcome of any study on inflation versus economic growth depends on how it is conducted. Most of the studies that examine the joint impact of both inflation and inflation uncertainty on economic growth, which is the most comprehensive approach, find the collective impact as unfavourable to economic growth.…”
Section: ▪ Inflationmentioning
confidence: 99%